Multifunctional Silk and Gelatin Composed Microneedle Patches for Enhanced Wound Healing - Fan, Lu; Wang, Li; Wang, Xiaoju; Li, Minli; Gu, Hongcheng; Zhang, Hongbo (John Wiley & Sons, 2025)
Wound healing has been a continuous critical focus in clinical practice, posing the ongoing challenges and burdens to patients. Current attempts tend to develop multi-drug loaded patches with spatial design. Herein, we present a multifunctional microneedle patch that integrates different drugs into separated regions for wound treatment. The microneedle patch is composed of silk fibroin-methacryloyl (SilMA) as the base, loaded with silver nanoparticles (AgNPs) and has gelatin methacryloyl (GelMA) tips loaded with vascular endothelial growth factor (VEGF). The backing is endowed with antimicrobial properties by AgNPs act as an antimicrobial barrier against bacterium invasion. In addition, the tips encapsulated with VEGF can effectively promote cell proliferation and angiogenesis, which is favorable for wound repair. Based on these characteristics, such an integrated microneedle system significantly prevented bacterial infection and promoted wound healing in vivo. Therefore, it is conceived that such a system can find more practical values in wound healing and other fields.